Proyectos escolares para el desarrollo de la interculturalidad en los estudiantes de cuarto año de E.G.B en la unidad educativa Fernando Daquilema, periodo 2021-2022 - Chimborazo Tuarez, Michelle Stephanie (2022)
The purpose of the following investigation is to analyze two variables: school projects and the development of Interculturality. The main objective allowed the analysis of school projects as a strategy to promote the development of Interculturality in fourth-year E.G.B students at the Fernando Daquilema Educational Unit, period 2021-2022. A qualitativequantitative approach was used as a methodology, that is, there was an approach to study and naturally interpret the phenomenon; descriptive, it allowed knowing the situations and characteristics of the study problem; documentary, since the information was collected from various sources of bibliographic research, scientific journals; with a population of 38 students. With an observation sheet evaluation instrument, it was possible to analyze the behavior of those involved in the teaching process in which there was great individual and group participation. The results obtained show that 47% of students almost always manage to differentiate between the various cultures that exist in Ecuador, and 74% always respect the cultural diversity of ethnic groups. On the other hand, 95% work with school projects and reflect on the topic discussed in class. Finally, it is concluded that determining the process for the development of Interculturality within the classroom through school projects is an initiative that requires the understanding of the teacher through the intercultural development in which the educational practices were carried out, adapting thus to school projects promoting an inclusive and integrating education.